From countercultural ecovillages to mainstream green neighbourhoods—a view on current trends in Denmark - Camilla Nielsen-Englyst; Quentin Gausset (npj Climate Action)
Abstract This paper describes how the ecovillage model for sustainability is currently spreading in Denmark through two different avenues. The first avenue is the creation of new eco-communities inspired by the ecovillage movement but created through top-down municipal support or from the side by the involvement of professional community builders. The second avenue is the spread of some aspects of the ecovillage model to mainstream housing neighbourhoods through the green neighbourhood movement, when neighbours meet, discuss what kind of sustainable interests they share, and act together to live more sustainably. Although eco-communities and green neighbourhoods will probably achieve less impressive carbon footprint reductions than ecovillages, they are exploring interesting avenues through which the spread of the ecovillage model, which is slow, costly, and exclusive, can be speed up and can trigger a mass movement that has the potential of bringing widespread changes.